'Oh no, not a group!' The factors that lonely or isolated people report as barriers to joining groups for health and well‐being. Issue 1 (24th May 2021) - Stuart, Avelie; Stevenson, Clifford; Koschate, Miriam; Cohen, Jessica; Levine, Mark
Abstract : Objectives: Belonging to groups can significantly affect people's health and well‐being for the better ('the social cure') or worse ('the social curse'). Encouraging people to join groups is a central component of the Social Prescribing movement; however, not everyone who might benefit from Social Prescribing aspires to participating in groups. This study aims to identify what barriers are preventing people from experiencing the associated health and well‐being benefits of group belonging. Method: Semi‐structured interviews analysed using reflexive thematic analysis. Participants were 11 white British people (aged 48‐86), 1 male and 10 female, recruited by a charity partner of a Social Prescribing project. Results: The themes derived from the interviews are as follows: (1) 'The dread, the fear of being in a group': When groups do not meet needs; (2) 'I can remember as quite a young child backing out of things': Accumulative barriers over the lifetime, and (3) 'I'm singing away and feeling terribly miserable': the challenges of fitting in with others in groups. The themes reflect how people can feel deterred from social interaction, which interferes with their ability to derive a sense of belonging or shared identity associated with the 'social cure'. Conclusions: A key challenge for Social Prescribing is to meet the social needs of people disinclined to join groups; groups can be detrimental to health and well‐being if there are barriers to integration. Alternative ways of structuring groups or activities may be more effective and can still avail of the belonging and identity associated with 'the social cure'.